AB0235 Relationship between the nottingham health profile and the health assessment questionnaire: evidence of validity in rheumatoid arthritis. (1st June 2001) - Emery, P; Woolley, JM; Chan, WW
Abstract : Background: Objectives: To assess the validity of the Nottingham Health Profile (NHP) health-related quality of life measure in subjects with rheumatoid arthritis. It was hypothesised that improvements in the Health Assessment Questionnaire (HAQ) would be significantly related to the NHP. Methods: Data on both the NHP and the HAQ were collected as part of a multicenter clinical trial conducted in Europe (n = 473). The NHP was administered at baseline and at weeks 12 and 24. The NHP consists of 38 items which assess physical mobility (MOB), pain (PAIN), energy (ENRG), sleep (SLP), emotional reactions (EMO), and social isolation (ISO). Both the NHP and the HAQ are scored so that lower scores indicate better HRQOL, and negative change scores indicate improvements. Validity was assessed by estimating the correlation between the scales of the NHP and the HAQ in cross-section and longitudinally (change score from baseline to week 24, Δ). It was hypothesised that both relationships would be positive, and that stronger relationships would be seen in the more physical HRQOL scales of the NHP (MOB and PAIN). Results: In cross-section (first row of the Table 1 ), all six of the NHP scales were positively and statistically significantly correlated with the HAQ. Additionally, as shown in the second row, the changes in all six of the NHP scales were positively and statistically significantly correlated with the change in the HAQ (D HAQ). As predicted, the highest correlations were seen in the more physical HRQOL scales, MOB and PAIN. Conclusion: These data support the validity of the Nottingham Health Profile as a measure of health-related quality of life in subjects with rheumatoid arthritis.